Origin identity and extended identity on the leaders of the ethnic organizations of agricultural workers in Sinaloa - Ortiz, Celso (2017)
Abstract: The objective is to know from the subjectivity of the subjects how origin and expanded identities are perceived from the migration, for which methodologically we conducted in-depth interviews, since the purpose research, as mentioned by Giddens (1998) is “to recreate the lifeworld of the social agent”. The main results of the research show that the origin and expanded identities of the indigenous leaders of the ethnic organizations of agricultural workers in Sinaloa play an important role, because they allow the analysis of the social limits that these social actors use to define themselves in front of the sectors of Sinaloan society that coexist daily. It is concluded that the concepts of origin identity and expanded identity allow to account for the ethnic-peasant and migrant-wage worker binomial that the indigenous leaders have been building through their migratory history.